Influence of body mass index on clinical estimation of fetal weight - Parveen, Sabeena; Manishaben, Balwani; K., Priya Ballal (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Estimation of fetal weight is essential for prenatal care and delivery management. Clinical methods, such as symphysiofundal height (SFH) assessment, and ultrasound-based techniques are commonly used for this purpose. Maternal body mass index (BMI) can influence fetal weight estimation accuracy, particularly in obese patient. In periphery where ultrasound facilities are not available clinical estimation of fetal weight plays very important role in antenatal care. This study was aimed to examine the impact of maternal BMI on the accuracy of clinical fetal weight estimation. Methods: This cross-sectional study included 800 pregnant women. Anthropometric measurements were collected, including weight, height, SFH, abdominal girth, and double abdominal fold thickness (DAFT). Fetal weight was estimated using clinical methods and compared with actual birth weight. Statistical analysis was performed using statistical package for the social sciences (SPSS) version 26.0. Results: Participants had a mean weight of 46.4 kg, height of 154.5 cm, and body mass index of 19.4 kg/m2. SFH×AG method yielded a mean birth weight estimation of 3.0 kg with an absolute error of 136 grams, while Johnson’s formula estimated 3.3 kg with an absolute error of 478 grams. double abdominal fold thickness measurements also showed variations in fetal weight estimation accuracy across different ranges. It was observed that as body mass index increased, the absolute error also increased. It was also noted that the SFH×AG formula was more accurate compared to Johnson’s formula. Conclusions: Relying solely on clinical estimation of fetal weight, especially in mothers with high body mass index, may be limited in accuracy. The SFH×AG method outperformed Johnson’s formula, particularly in cases influenced by body mass index. Complementary methods, such as ultrasound-based techniques, are recommended to enhance accuracy, especially in obese pregnant women.